Effect of training phase on 8OHdG with menstrual cycle in female athletes - Momma, R.; Shimizu, K. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: The Menstrual cycle influences change physical and psychological condition and performance in female athletes. Previous studies have reported that increased stress and anxiety during the luteal and menstrual phases, as well as decreased agility performance, endurance performance, intermittent endurance performance. 8-hydroxy-2-deoxy-guanosine (8OHdG) excreted into the urine is a marker of oxidative stress, and it has been reported to be associated with fatigue, psychological stress, and exercise. It has also been reported that 8OHdG changes with the menstrual cycle. However, it is unclear how the training phase (competitive phase, preparation phase, transition phase) influences 8OHdG with the menstrual cycle in female athletes. Thus, the purpose of this study was to investigate the effect of training phase on the 8OHdG with menstrual cycle in female athletes.